"Foreign body" of the common bile duct, "post necrotic cholecystitis, dissecting and exfoliatrix": pathological anatomical collaboration Dr J. F. Casinelli - Asiner, Boris (Cirugía del Uruguay, 2020)
Presented at session 26th August 1959